1993
DOI: 10.1111/j.1438-8677.1993.tb00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, Transport and Storage of Cardenolides in Foxglove. Cardenolide Sinks and Occurrence of Cardenolides in the Sieve Tubes of Digitalis lanata1

Abstract: Cardiac glycoside transport was investigated on the organ and whole plant level. Uptake experiments were carried out with shoot and root cultures of Digitalis lanata. In both systems primary cardenolides, i.e., those with a terminal glucose in their oligosaccharide side chain, were taken up against their concentration gradient, whereas the glucose‐free secondary cardenolides were not. Active uptake of primary cardenolides was further evidenced by KCN inhibition of uptake. Using plantlets grown in vitro the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Therefore, the loading of both Suc and antirrhinoside into the phloem in A. barclaiana must be energized. This is consistent with the following observations: First, H 1 /Suc symporters from A. barclaiana were cloned and their function in Suc uptake confirmed by functional expression and complementation in yeast (Saccharomyces cerevisiae; Knop, 2001); second, transfer of glucosides via the plasma membrane against their concentration gradient has been demonstrated in another Scrophulariaceae species, Digitalis lanata (Christmann et al, 1993), and recently, the Suc transporter AtSUC2 was shown to accept a broad range of glucosides as substrates (Chandran et al, 2003); and third, antirrhinoside and Suc were both present in the apoplast and their apoplastic concentrations in leaves with blocked translocation increased 3-fold and 6-fold, respectively. Thus, in A. barclaiana, Suc and antirrhinoside are likely to be actively loaded into the phloem from the apoplast, perhaps mainly via TCs.…”
Section: Comparison Of Sugar Concentrations In Cytoplasm Of Mesophyllsupporting
confidence: 81%
“…Therefore, the loading of both Suc and antirrhinoside into the phloem in A. barclaiana must be energized. This is consistent with the following observations: First, H 1 /Suc symporters from A. barclaiana were cloned and their function in Suc uptake confirmed by functional expression and complementation in yeast (Saccharomyces cerevisiae; Knop, 2001); second, transfer of glucosides via the plasma membrane against their concentration gradient has been demonstrated in another Scrophulariaceae species, Digitalis lanata (Christmann et al, 1993), and recently, the Suc transporter AtSUC2 was shown to accept a broad range of glucosides as substrates (Chandran et al, 2003); and third, antirrhinoside and Suc were both present in the apoplast and their apoplastic concentrations in leaves with blocked translocation increased 3-fold and 6-fold, respectively. Thus, in A. barclaiana, Suc and antirrhinoside are likely to be actively loaded into the phloem from the apoplast, perhaps mainly via TCs.…”
Section: Comparison Of Sugar Concentrations In Cytoplasm Of Mesophyllsupporting
confidence: 81%
“…Several secondary plant products, including cyanogenic glucosides (Mùller and Seigler 1998) and cardenolides (Christmann et al 1993), are only transported within the plant in a glycosylated form. In the case of the cyanogenic glucoside linamarin in Hevea brasiliensis, where the diglucoside but not the monoglucoside or aglycone is the transport form, the substrate speci®city of apoplastic beta-glucosidases restricts the extracellular transport of the monoglucoside (Gruhnert et al 1994).…”
Section: Transportationmentioning
confidence: 99%
“…The long-distance transport of primary cardenolides from the leaves to the roots or to etiolated leaves was demonstrated. It was established that the phloem but not the xylem is a transporting tissue for cardenolides (84). To summarize, it seems as if primary cardenolides may serve as both the transport and the storage form of cardenolides.…”
Section: Compartmentalization Of Cardenolide Formationmentioning
confidence: 99%